Citizen Centricity in Public Policy Making Approaches, Mechanisms, and Beyond - Karkin, Naci; Göçoğlu, Volkan (Contributions to Public Administration and Public Policy, 2025)
XVI, 172 p. 5 illus., 4 illus. in color.